2008
DOI: 10.1051/0004-6361:200810778
|View full text |Cite
|
Sign up to set email alerts
|

Structure function of the UV variability of Q0957+561

Abstract: We present a detailed structure function analysis of the UV variability of Q0957+561. From optical observations in the 2005−2007 seasons, we constructed normalized structure functions of the quasar luminosity at restframe wavelengths λ ∼ 2100 Å and λ ∼ 2600 Å. Old optical records (1995−1996 seasons) also allow the structure function to be obtained at λ ∼ 2100 Å, but 10 years ago in the observer's frame. These three structure functions are then compared to predictions of both simple and relatively sophisticated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 48 publications
3
13
0
Order By: Relevance
“…Differences between time coverages, gaps and artifacts in the g ( ~ 2100 Å) and r ( ~ 2600 Å) bands are the most plausible causes of subtle differences between both growths [7]. Apart from this achromaticity, [7] showed that ~ 0.7, so a reverberation scenario could explain the variability of Q0957+561. Initial slopes 0.5 and ~ 1 are not favoured by the LQLM observations (see the dashed line in Fig.…”
Section: Lqlm Data Of Q0957+561mentioning
confidence: 96%
See 4 more Smart Citations
“…Differences between time coverages, gaps and artifacts in the g ( ~ 2100 Å) and r ( ~ 2600 Å) bands are the most plausible causes of subtle differences between both growths [7]. Apart from this achromaticity, [7] showed that ~ 0.7, so a reverberation scenario could explain the variability of Q0957+561. Initial slopes 0.5 and ~ 1 are not favoured by the LQLM observations (see the dashed line in Fig.…”
Section: Lqlm Data Of Q0957+561mentioning
confidence: 96%
“…This showed a steep growth, so here we want to re-discuss the variability structure and to compare it with the = 0.7 law. The structure function SF(L) at restframe lag is given by (e.g., [7]) (1), are computed as the standard deviations of the means (averaged sums) for the different time lag bins. Thus, the uncertainties are likely underestimated because not all pairs of data in a given bin are independent [3].…”
Section: Lqlm Data Of Sbs 0909+532mentioning
confidence: 99%
See 3 more Smart Citations